(untitled) (Journal of Geography and Environmental Management, 2016)
UNOOSA/UN-SPIDER and the program mandate have been introduced. A brief review of the published work about the use telecommunications for disasater management and emergency response is given. The current satellite communication technologies for disaster management and emergency response have been listed for the appropriate response teams and efforts. The approach of UN-SPIDER to fullfill its mission is summarized.